An Empirical Study on Food and Beverage Service Quality and Customer Satisfaction in Star Graded Hotels in Dambulla - Bandara WMAH; Dahanayake SNS (International Journal of Engineering and Management Research, 2020)
The hotel industry is one of the integral constituents in the flourishing tourism industry and is extremely competitive. In this competitive arena, service quality has become a crucial success factor in maintaining hotel standards. A strong, sustainable, outstanding service industry requires good service quality standards. However, due to the intangible nature of service products, measuring service quality is substantially challengeable than measuring the quality of physical products. Hence, this study attempts to investigate the impact of food and beverage service quality on customer satisfaction in the star graded hotels. Dambulla is one of the major tourist destinations in Sri Lanka, has been identified as the study area. A total of 150 foreign departure tourists who have visited three and above star graded hotels in the respective area were selected through a convenient sampling technique. A widely accepted SERVQUAL model was utilized to ascertain the findings. Primary data were collected through a self-administered structured questionnaire. Descriptive, frequency, Pearson correlation, and multiple regression analysis were conducted to analyze data using SPSS. The results reveal that there is a positive significant impact of tangibility, reliability, responsiveness, assurance of food and beverage service quality on customer satisfaction in the star graded hotels in Dambulla area. On the contrary, empathy shows that there is no impact on customer satisfaction. Moreover, tangibility is the most influential service quality attribute that affects customer satisfaction. Thus, the authorities must pay their attention towards improving the tangible evidence such as staff attires and appearance, aesthetic upkeep of interior and exterior, and provide reliable service for their guests with greater customer care.